2010
DOI: 10.1186/1471-2334-10-28
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box-1 protein, lipopolysaccharide-binding protein, interleukin-6 and C-reactive protein in children with community acquired infections and bacteraemia: a prospective study

Abstract: IntroductionEven though sepsis is one of the common causes of children morbidity and mortality, specific inflammatory markers for identifying sepsis are less studied in children. The main aim of this study was to compare the levels of high-mobility group box-1 protein (HMGB1), Lipopolysaccharide-binding protein (LBP), Interleukin-6 (IL-6) and C-reactive protein (CRP) between infected children without systemic inflammatory response syndrome (SIRS) and children with severe and less severe sepsis. The second aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…have also shown that increases in HMGB1 concentrations, but not in those of sCD163, correlate with WBC counts and concentrations of other proinflammatory indicators and CRP . CRP is reportedly significantly positively correlated with serum HMGB1 concentrations according to some studies ; however, others found no correlations between HMGB1 and CRP . Neither HMGB‐1 nor sCD163 concentrations correlated with WBC count and CRP in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…have also shown that increases in HMGB1 concentrations, but not in those of sCD163, correlate with WBC counts and concentrations of other proinflammatory indicators and CRP . CRP is reportedly significantly positively correlated with serum HMGB1 concentrations according to some studies ; however, others found no correlations between HMGB1 and CRP . Neither HMGB‐1 nor sCD163 concentrations correlated with WBC count and CRP in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…The best cut-off used in this study was 15 pg/mL, which gave a sensitivity of 75% and a specificity of 91% for confirming bacterial infection. Previous reports suggested that serum cytokines appeared in a temporal sequence after endotoxin injection 21 serum IL-6 levels between groups in which blood was drawn earlier (0-36 hours) compared to those who were sampled later (36-72 hours). 20 This observation implies that IL-6 has a tendency to be present in the circulation for a considerable length of time following infection.…”
Section: Discussionmentioning
confidence: 93%
“…IL-6 serum levels are higher in children diagnosed with sepsis than in patients with noninfectious systemic inflammation only, (43,44) and its diagnostic accuracy increases when combined with other diagnostic biomarkers, including CRP, for example. (43) Furthermore, among children with sepsis, an increase in IL-6 level is associated with more severe cases, (45) and its use in clinical practice can provide a good predictor of severe sepsis.…”
Section: Introductionmentioning
confidence: 99%